Iconographic study for the integration of a history of knowledge - Crippa, Giulia (InCID: Revista de Ciência da Informação e Documentação, 2010)
This paper pretend to discuss a group of images that illustrate the subject of university, through scenes in which the main character is the Master in his duty of teaching students. These scenes are mainly found in funerary monuments from the beginning of the XIVth century, located mainly in Bologna (Italy) at the Medieval Museum of the city and in some churches on the national territory. They bring to the monumentary space of religious memory – the cemetery – a new social actor, recently appeared in urban space, dedicated to a profession which aim was the pecus, the gain, and the fame: the Laic Master. The paper draws the historical trajectory of the institutionalization of knowledge of the so called “philosopher”, suspiciously saw by the ecclesiastic elements, who, until then, were the main characters of the arquitecture of medieval knowledge. The images produced by the monuments, representing the social and professional position of the Laic Masters, is, nonetheless, the results of the search for legitimate spaces of intellectual reward in university, through conflicts that develop and manifest through the XIIIth century. This is when the odification of the curricula, already proposed since the middle XIIth century by personalities such as Hugo of Saint Victor, results in a larger base of teachers, actively engaged in faculties such as medicine, law and, in a great deal, such as liberal and mechanical arts.